2017
DOI: 10.1021/acs.joc.7b00210
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Access to d-Sarmentose Units Enables the Total Synthesis of Cardenolide Monoglycoside N-1 from Nerium oleander

Abstract: Herein we present a chemical approach for the ready preparation of d-sarmentosyl donors enabling the first total synthesis and structure validation of cardenolide N-1, a challenging 2,6-dideoxy-3-O-methyl-β-d-xylo-hexopyranoside extracted from Nerium oleander twigs that displays anti-inflammatory properties and cell growth inhibitory activity against tumor cells. The strategy highlights the synthetic value of the sequential methodology developed in our group for the synthesis of 2-deoxyglycosides. Key steps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The stereochemistry of the C-4 substituent had little effect on the selectivity although the slight improvement in the d - allo configuration may be explained by the less entropically disfavored β-transition state resulting from the stabilizing pseudoaxial positioning of OBn in the 3 H 4 conformer ( Scheme 1 ). 11,17 Elaboration of 7 and 8 under conventional deiodination and debenzylation conditions 2 afforded final 2-deoxy cardiac glycosides 9 and 10 in excellent yields (up to 95%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stereochemistry of the C-4 substituent had little effect on the selectivity although the slight improvement in the d - allo configuration may be explained by the less entropically disfavored β-transition state resulting from the stabilizing pseudoaxial positioning of OBn in the 3 H 4 conformer ( Scheme 1 ). 11,17 Elaboration of 7 and 8 under conventional deiodination and debenzylation conditions 2 afforded final 2-deoxy cardiac glycosides 9 and 10 in excellent yields (up to 95%).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, cholesterol 3c was subjected to the same oxidation/glycosylation sequence with the more challenging 2,6-dideoxy glycosyl donor 5b to afford 2,6-dideoxy-2-iodo- d - allo derivative 11 with good stereoselectivity (20 : 1 β/α) 2,9 d and moderate overall yield (52%). Final products 9 and 10 as well as their precursors 7, 8 and 11 adopted a 4 C 1 conformation as determined by NOE experiments and the analysis of diagnostic coupling constants ( 3 J 1,2 ∼ 9 Hz and 1 J C1–H1 ∼ 163 Hz).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical synthesis of steroid glycosides is hindered by many drawbacks, such as poor regio- and stereoselectivities, requirement of protection and deprotection steps, use of toxic catalysts, and production of chemical waste. Instead, biocatalysis has been recognized as an alternative way to solve these problems, which is environment-friendly and cost-effective. , It was reported that the cell suspension cultures of several specific plant species are capable of glycosylation of cinobufagin, such as Catharanthus roseus, Platycodon grandiflorus, and Saussurea involucrata. However, low yields and generation of byproducts make it hard to purify the target steroid glycosides. Recently, significant progress has been made in enzymatic glycosylation of steroid compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a slowing of the heart rate and a positive inotropic response, directly counteracting the effects of congestive heart failure.In addition, recent investigations have shown that 14β-hydroxysteroids possess a wide spectrum of biological activities including anticancer, 4,7,8 immunoregulatory, antiinflammatory and antihypertensive properties. [9][10][11] Recently, the drug-oriented design and synthesis of 14β-hydroxysteroids has received considerable attention important results include [12][13][14] the preparation of the 17a[(aminoalkoxy)imino] alkyl analogues of digitoxigenin by partial synthesis starting with androstane derivatives. These are potent inhibitors of Na + , K + -ATPase (Fig.…”
mentioning
confidence: 99%